Pesniška pleosemija - Snoj, Vid (Primerjalna književnost, 2016)
The study distinguishes the abundance of meaning in poetic discourse from the multitude of meaning in everyday discourse. Based on the example of a short poem by Rilke, it demonstrates what this abundance in poetry is in which several meanings are not reducible to a single meaning.
Keywords: Rilke, Rainer Maria, 1875-1926; poezija; pesniški jezik; pesniška govorica; vsakdanja govorica; dvoumnost; mnogopomenskost; večpomenskost